Implication of synaptotagmins 4 and 7 in activity-dependent somatodendritic dopamine release in the ventral midbrain - Benoît Delignat-Lavaud; Charles Ducrot; Willemieke Kouwenhoven; Nina Feller; Louis-Éric Trudeau (Open Biology, 2022)
Dopamine (DA) neurons can release DA not just from axon terminals, but also from their somatodendritic (STD) compartment through a mechanism that is still incompletely understood. Using voltammetry in mouse mesencephalic brain slices, we find that STD DA release has low capacity and shows a calcium sensitivity that is comparable to that of axonal release. We find that the molecular mechanism of STD DA release differs from axonal release with regard to the implication of synaptotagmin (Syt) calcium sensors. While individual constitutive knockout of Syt4 or Syt7 is not sufficient to reduce STD DA release, the removal of both isoforms reduces this release by approximately 50%, leaving axonal release unimpaired. Our work unveils clear differences in the mechanisms of STD and axonal DA release.